Housing, pasture management and roughage supplementation on the pre-weaning growth of goats in the tropical Northeast of Brazil - Oliveira, Ederlon R.; Lima, Francisco A. Melo; Pant, K. P. (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was undertaken with 100 adult does of an undefined but most common type of goats called "sem raça definida" (SRD) The does were divided into four equal groups (each of 25 does) of comparable age and weights. These were allotted to four treatments as follows: native "caatinga" pastures with either (1) ground floor or (2) raised slatted floor system of housing; cleared pastures with raised floor system of housing either (3) without or (4) with ad libitum supplementation of green elephant grass (Pennisetum purpureum Schum.) only during dry months. Data on 250 kids born to these does over a period of two years and maintained under the same treatment as their mothers were analysed for their pre-weaning growth were studied. Until three weeks of age, the body weights were almost identical among treatments. Significant treatment effects appeared around four weeks and consistently increased till weaning at 112 days. A comparison of treatments showed that, for the growth of kids, the ground floor system of housing was better than the raised floor system, and cleared pastures had a distinct advantage over native "caatinga" pastures. The best results were obtained in the group supplemented with elephant grass during four very dry months. It appears that the best growth in the local agroclimatic conditions can be obtained when kids are maintained on the ground floor system of housing and cleared pastures with supplementation in the very lean months.
Keywords: kids; ground floor; slatted floor; green elephant grass; dry season